Differences in students' metacognitive strategy knowledge, motivation, and strategy use: A typology of self-regulated learners. Issue 3 (3rd May 2016) - Karlen, Yves
ABSTRACT: Metacognitive strategy knowledge, motivation, and learning strategies play an important role in self-regulated learning (SRL). However, little is known about different profiles of self-regulated learners in schools that prepare students for the university entrance certificate. The aim of this study was to examine intraindividual differences in the patterns of students' SRL. In this 2-wave longitudinal study, 897 students were involved. Latent class analyses revealed four-cluster solutions at the beginning as well as at the end of the school year. Maximal self-regulated learners with the highest levels on all cognitive, metacognitive, and motivational components of SRL reported the highest grades in the academic subject of German (first language) at both measurement points, followed by motivated and strategic learners. Students with a low level on several SRL components reported the lowest grades. Further, the results indicated changes in profiles of SRL over time.